2017
DOI: 10.1007/s00247-017-3946-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and characteristics of pulmonary nodules in children at computed tomography

Abstract: BackgroundNormative data on pulmonary nodules in children without malignancy are limited. Knowledge of the frequency and characteristics of pulmonary nodules in healthy children can influence care decisions in children with malignant disease.ObjectiveTo provide normative data concerning the frequency and characteristics of pulmonary nodules on computed tomography (CT) in young children.Materials and methodsAll children ages 1 year–12 years who underwent chest CT after high-energy trauma were retrospectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…Results show a small to medium correlation between lymph node size and age for Levels IV to VI. This finding is in line with earlier published normal measurements of chest lymph nodes in children [12]. Because the differences in lymph node size with increasing age are small, we believe that age-dependent normal values are not necessary in clinical practise.…”
Section: Discussionsupporting
confidence: 92%
“…Results show a small to medium correlation between lymph node size and age for Levels IV to VI. This finding is in line with earlier published normal measurements of chest lymph nodes in children [12]. Because the differences in lymph node size with increasing age are small, we believe that age-dependent normal values are not necessary in clinical practise.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports, we found that incidental nodules are detected in otherwise healthy children 3 . Even in those who had initial imaging due to respiratory symptoms, the nodule(s) may still be an incidental finding.…”
Section: Discussionsupporting
confidence: 91%
“…Previous pediatric studies assessed the incidence and characteristics of incidental nodules when chest computed tomography (CT) was performed on healthy children evaluated for trauma. Samim et al detected at least one nodule in 38% of pediatric trauma patients who had a chest CT, with substantial per patient interobserver agreement 3 . Renne et al 4 detected at least one nodule in 33% of pediatric trauma patients and concluded that nodules are detected frequently in children without known malignant disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the actual incidence of pulmonary nodules, doctors' different detection and reporting of pulmonary nodules may be one of the possible reasons for the great variation. Samim et al (17) reported the agreement between two radiologists with respect to identification of pulmonary nodules was 0.78 kappa value in patient-based analysis and 0.40 in lobe-based analysis.…”
Section: Discussionmentioning
confidence: 99%